Hygiene on maternity units: lessons from a needs assessment in Bangladesh and India. Issue 1 (1st December 2016) - Cross, Suzanne; Afsana, Kaosar; Banu, Morsheda; Mavalankar, Dileep; Morrison, Emma; Rahman, Atiya; Roy, Tapash; Saxena, Deepak; Vora, Kranti; Graham, Wendy J
Abstract : Background: As the proportion of deliveries in health institutions increases in low- and middle-income countries, so do the challenges of maintaining standards of hygiene and preventing healthcare-associated infections (HCAIs) in mothers and babies. Adequate water, sanitation, and hygiene (WASH) and infection prevention and control (IPC) in these settings should be seen as integral parts of the broader domain of quality care. Assessment approaches are needed which capture standards for both WASH and IPC, and so inform quality improvement processes. Design: A needs assessment was conducted in seven maternity units in Gujarat, India, and eight in Dhaka Division, Bangladesh in 2014. The WASH & CLEAN study developed and applied a suite of tools – a 'walkthrough checklist' which included the collection of swab samples, a facility needs assessment tool and document review, and qualitative interviews with staff and recently delivered women – to establish the state of hygiene as measured by visual cleanliness and the presence of potential pathogens, and individual and contextual determinants or drivers. Results: No clear relationship was found between visually assessed cleanliness and the presence of pathogens; findings from qualitative interviews and the facility questionnaire found inadequacies in IPC training for healthcare providers and no formal training at all for ward cleaners. Lack of written policies and protocols, and poor monitoring and supervision also contributed to suboptimal IPC standards. Conclusions: Visual assessment of cleanliness and hygiene is an inadequate marker for 'safety' in terms of the presence of potential pathogens and associated risk of infection. Routine environmental screening of high-risk touch sites using simple microbiology could improve detection and control of pathogens. IPC training for both healthcare providers and ward cleaners represents an important opportunity for quality improvement. This should occur in conjunction with broader systems changes, including the establishment of functioning IPC committees, implementing standard policies and protocols, and improving health management information systems to capture information on maternal and newborn HCAIs.